Protective effect of lycopene and grape seed extract against salbutamol toxicity on myocardial tissue - Shams, Gamal E.; Abd El-latief, Suhair A.; Abdelrahman, Reem I. (Journal of Advanced Veterinary Research, 2024)
Cardiovascular toxicity includes damage to the heart resulting from inflammation, oxidative stress, and toxin-induced abnormalities in electrophysiology, and muscle damage. The current study set out to investigate the potential cardioprotective properties of lycopene (LCP) and grape seed extract (GSE) as potential novel therapies to counteract the cardiotoxicity caused by salbutamol. Histopathological and immunohistochemical analysis were used to achieve this. Male albino rats weighing between (150_180g b.wt) were randomly divided into six sets, each containing seven rats. Group I received saline and kept as a control group. Group II was given oral administration of salbutamol (65 mg/kg b.wt.) for 2 consecutive days. Group lll received oral dose of LCP (1 mg/kg b.wt.) for three weeks. Group IV was given oral dose of GSE (100 mg/kg b.wt.) for three weeks. Group V was pretreated orally with LCP for three weeks followed by salbutamol oral administration (65 mg/kg b.wt.) for two consecutive doses. Group VI was pretreated orally with GSE (100 mg/kg b.wt.) for three weeks followed by salbutamol oral administration (65 mg/kg b.wt.) for two consecutive doses. All treatments were administered once daily by oral route using gastric tube. Results revealed that salbutamol induced cardiac damage manifested by congestion of myocardial blood vessels, intermuscular hemorrhages, endocardial degenerative changes, microcalcification and subendocardial congestion and hemorrhage, focal cardiomyocytes hyalinization with nuclear peripheralization and pyknosis and individual cellular apoptosis. In comparison with salbutamol group, pre-treatment of rats with GSE demonstrated a moderate ameliorative effect comparable to that of LCP pretreated group; however the residual tissue changes are little bit worse. Immunohistochemistry results supported the histopathological investigations. In conclusion, pre-administration of GSE and LCP provide potential cardioprotective effects by reducing salbutamol-induced cardiac damage linked to alterations in histopathology and immunohistochemistry.